Understanding barriers to home‐based and self‐care in‐center hemodialysis. Issue 2 (28th September 2015) - Yau, May; Carver, Michelle; Alvarez, Luis; Block, Geoffrey A.; Chertow, Glenn M.
Abstract: Despite superior outcomes and lower associated costs, relatively few patients with end‐stage renal disease undergo self‐care or home hemodialysis. Few studies have examined patient‐ and physician‐specific barriers to self‐care and home hemodialysis in the modern era. The degree to which innovative technology might facilitate the adoption of these modalities is unknown. We surveyed 250 patients receiving in‐center hemodialysis and 51 board‐certified nephrologists to identify key barriers to adoption of self‐care and home hemodialysis. Overall, 172 (69%) patients reported that they were "likely" or "very likely" to consider self‐care hemodialysis if they were properly trained on a new hemodialysis system designed for self‐care or home use. Nephrologists believed that patients were capable of performing many dialysis‐relevant tasks, including: weighing themselves (98%), wiping down the chair and machine (84%), clearing alarms during treatment (53%), taking vital signs (46%), and cannulating vascular access (41%), but thought that patients would be willing to do the same in only 69%, 34%, 31%, 29%, and 16%, respectively. Reasons that nephrologists believe patients are hesitant to pursue self‐care or home hemodialysis do not correspond in parallel or by priority to reasons reported by patients. Self‐care and home hemodialysis offer several advantages to patients and dialysis providers. Overcoming real and perceived barriers with new technology, education and coordinated care will be required for these modalities to gain traction in the coming years.